On maximal inequalities for some jump processes - Pavel V. Gapeev (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
We present a solution to the considered in [5] and [22] optimal stopping problem for some jump processes. The method of proof is based on reducing the initial problem to an integro-differential free-boundary problem where the normal reflection and smooth fit may break down and the latter then be replaced by the continuous fit. The derived result is applied for determining the best constants in maximal inequalities for a compound Poisson process with linear drift and exponential jumps.
Keywords: 330